2017
DOI: 10.1016/j.pse.2017.02.003
|View full text |Cite
|
Sign up to set email alerts
|

The impact of perseverance and passion for long term goals (GRIT) on educational achievements of migrant children: Evidence from Tatarstan, Russia

Abstract: This article empirically studies the impact of perseverance and passion for long term goals (GRIT) on educational achievements. Specifically, the study compares GRIT levels between migrants and native school students, and tests the role of GRIT in explaining school achievements of migrants. Based on regression analysis and using a sample of 2,003 ninth graders, including 178 migrants from the Republic of Tatarstan, Russia, the results did not suggest an educational gap between native students and first generat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 16 publications
(45 reference statements)
0
9
0
1
Order By: Relevance
“…In terms of the criterion‐related validity of Grit‐O and Grit‐S, the weighted mean correlation of Grit‐O was 0.13, while that of Grit‐S was 0.17. One study used Tovar‐García's () 15‐item Grit Scale and one used five grit‐related items in OECD (Huang & Zhu, ). To assess the two facets of grit, 13 studies used the Grit‐S scale while seven used the Grit‐O scale.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In terms of the criterion‐related validity of Grit‐O and Grit‐S, the weighted mean correlation of Grit‐O was 0.13, while that of Grit‐S was 0.17. One study used Tovar‐García's () 15‐item Grit Scale and one used five grit‐related items in OECD (Huang & Zhu, ). To assess the two facets of grit, 13 studies used the Grit‐S scale while seven used the Grit‐O scale.…”
Section: Resultsmentioning
confidence: 99%
“…Among 54 studies that examined the effect of overall grit on students’ academic achievement, more than half (35 studies) reported significant positive results (Akos & Kretchmar, ; Cosgrove et al, ; Duckworth & Quinn, ; Duckworth et al, ; Dumfart & Neubauer, ; Farroll, ; Hill, ; Huang & Zhu, ; B. C. Lee, ; Lee & Sohn, ; Li et al, ; Lin & Chang, ; Mason, ; Muenks et al, ; Sheehan, ; Strayhorn, ; Tovar‐García, ; Wang et al, ; Williams, ), whereas one study reported a significant negative result (Climer, ). Six studies reported mixed results (Al‐Mutawah & Fateel, ; Cross, ; Kelly et al, ; O'Neal et al, ; Pate et al, ; Rojas, ) and eight studies reported nonsignificant results (Batres, ; Bazelais, Lemay, & Doleck, ; Engel, ; Flanagan & Einarson, ; Palisoc et al, ; Saunders‐Scott et al, ; Smith, ; Zurlo, ).…”
Section: Resultsmentioning
confidence: 99%
“…There has been a considerable body of literature showing how grit may relate to school-related performance and behaviors. Gritty students are more likely to have higher levels of general academic achievement among university students in the United States (Duckworth et al, 2007 ; Duckworth and Quinn, 2009 ; Akos and Kretchmar, 2017 ); high school students in mainland China (Li et al, 2018c ), secondary education students in the United States (Cosgrove et al, 2018 ; Park et al, 2018 ), Germany (Schmidt et al, 2019 ), Austria (Dumfart and Neubauer, 2016 ), and Russia (Tovar-García, 2017 ); course-specific academic achievement among military cadet samples in the United States (Mayer and Skimmyhorn, 2017 ); literacy achievement among primary school students (O'Neal et al, 2018 ); academic achievement in science in secondary school students in Australia (Hagger and Hamilton, 2019 ); performance in a national spelling bee contest (Duckworth et al, 2010 ); retention in selected undergraduate students in the United States (Saunders-Scott et al, 2018 ); academic engagement in selected university and high school students in the Philippines (Datu et al, 2016 , 2018b ); academic self-efficacy among university students in the Philippines (Datu et al, 2017a ) and the United States (Renshaw and Bolognino, 2016 ); generalized self-efficacy (Renshaw and Bolognino, 2016 ); intellectual self-concept among selected twin sample in the United States (Tucker-Drob et al, 2016 ); emotional engagement among dual language learners in the United States (O'Neal et al, 2018 ); school-related motivation among Filipino, American, and Mexican American students (Eskreis-Winkler et al, 2014 ; Yeager et al, 2014 ; Piña-Watson et al, 2015 ; Datu et al, 2018b ); learning engagement in selected mainland Chinese adolescents (Lan and Moscardino, 2019 ); test motivation among twins in the United States (Tucker-Drob et al, 2016 ); deliberate practice in optional and required practice in specific sports domains among selected athletes mostly from the North American context (Tedesqui and Young, 2017 ); satisfaction with e-learning systems among university students in Portugal (Aparicio et al, 2017 ); college satisfaction (Bowman et al, 2015 ); leadership skills among military cadets (Mayer and Skimmyhorn, 2017 ); mastery orientation (Tucker-Drob et al, 2016 ); meaningfulness of academic activities (Yeager et al, …”
Section: Performance Psychological and Physical Benefits Of Gritmentioning
confidence: 99%
“…Mounting evidence has suggested that resilience may act as a promotive factor to buffer the detrimental effects of adversity among migrant adolescents in China (Ye et al, ; Zhu, Guo, Pan, & Lin, ). In Russia, GRIT, as a component of resilience, was found to account for the academic achievements among migrant adolescents (Tovar‐García, ). Taken together, these studies have documented the protective function of resilience in reducing the negative effects on migrant adolescents.…”
Section: Adolescent's Resilience As a Personal Protective Factormentioning
confidence: 99%